Analisa Simulasi Unjuk Kerja Filter Aktif Cascaded Multilevel Inverter Untuk Mengurangi Efek Harmonisa Keluaran Hybrid Bidirectional Inverter 1500 Watt - Ade Maulana; Amir Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Harmonics cause voltage distortion that can result in electrical equipment becomes hot quickly, the power factor is low, interference with the equipment that use relays for switching and measurement accuracy kWh-meter induction type will be reduced, therefore harmonics requires serious attention, to cope with a wave distorted would require a technology that has the function of fixing the waves, this technology is called filter. The use of filters to reduce harmonic been widely recommended to overcome these problems. This final project describes one harmonic filter configuration, that’s called Active Filter parallel configuration, the method used is Cascaded Multilevel Inverter. The results of the simulation system design and form of the value of THD (Total Harmonic Distortion). THD value on systems that use an active filter Cascaded Multilevel Inverter showed a significant decrease compared to the system without the addition of a filter on Bidirectional Hybrid Inverter 1500 watts.Key Word: Harmonic, Active Filter, Cascaded Multilevel Inverter